The use of cloud computing and its effect on organisational performance in the public sector - Naidoo, Wesley (University of the Witwatersrand, Johannesburg, 2024)
Cloud computing is changing how public sectors work, making things faster and better. This paper looks at how cloud computing affects how well public organisations do their jobs, considering both money-related and other benefits. Cloud computing is essential for public services because it can make them work better and give better services to people. Nevertheless, understanding how it helps is difficult, especially with the public sector's unique rules and challenges. Cloud computing is one of the new technologies that has gained prominence in recent years. Even though the value associated with this technology has been widely researched, especially for large enterprises, the rate at which public sector entities use cloud computing remains low. This research sought to explore and describe the use of cloud computing and its effect on organisational performance in the public sector. To understand the problems, factors influencing the use of cloud computing and its use on organisational performance were investigated, considering both financial and non-financial factors. The study utilised the extended Technology Organisation Environment (TOE) and Resource-based view (RBV) framework (Gangwar,2017) as the theoretical lens to understand the cloud computing phenomenon. Methodologically, this study employed online surveys administered through the Qualtrics online survey platform to gather data. These surveys sought to extract invaluable insights into the use of cloud computing and its effect on organisational performance in the public sector. The main factors identified as necessary in using cloud computing are human resources, business resources, technology resources, change management, leadership, policy and regulation, customer performance, operational performance, and financial performance. The model was tested through a cross-sectional design using data collected from a sample (N=400) of individuals employed in the public sector in South Africa using matched data collected over a period of approximately 16 weeks apart. Structural equation modelling with AMOS was used for all model testing. This study applied a complex approach to data analysis using descriptive statistics, correlation analysis, confirmatory factor analysis, and multiple regression through structural equation modelling to provide an analysis of the various variables identified. The iii research showed significant relationships between cloud computing use and leadership, policy and regulation, human resources, technology and business resources. This confirmed the first objective of understanding the factors that influence the use of cloud computing in the public sector in South Africa. The following significant result showed that this is a new contribution, as previous studies measured non-financial performance as a single item instead of expanding it to include customer, operational, and financial performance. The testing of the model thus contributes to developing a theory that explains the mechanisms through which cloud computing influences organisational performance and extends our understanding of the organisational conditions under which cloud computing usage is most important to performance. The empirical results confirm that cloud computing use is vital to affect organisational performance in the public sector. The study further contributes much-needed evidence of the relationships addressed by the influence of cloud computing on a holistic perspective of organisational performance, encompassing operational, customer, and financial aspects. This study aims to provide industry practitioners with practical insights and actionable strategies to justify investments in cloud computing systems and to improve how cloud systems are used.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cloud Computing; Organisational performance; Technology; Organisational environmental framework; UCTD; SDG-8: Decent work and economic growth